Check It: A Community-Based Chlamydia Seek, Test, and Treat Program for Young Black Men Who Have Sex With Women in New Orleans, Louisiana. Issue 1 (26th January 2022) - Schmidt, Norine; Gomes, Gérard; Scott, Glenis; Wise, Breon; Craig-Kuhn, Megan Clare; Lederer, Alyssa M.; Martin, David H.; Kissinger, Patricia J.
Abstract : Seek, test, and treat community-based chlamydia screening for young Black men is feasible with community input, tailored implements, and a modest monetary incentive and can help reduce Chlamydia trachomatis disparities. Supplemental digital content is available in the text. Abstract : Background: Check It is a novel, bundled, community-based seek, test, and treat Chlamydia trachomatis (Ct) screening program for 15- to 24-year-old Black men in New Orleans who have sex with women. The program design addressed barriers and facilitators to Ct screening/treatment by enlisting trusted community partners, incorporating participant input, providing free index/partner expedited treatment, developing relatable marketing materials and an educational Web site, encouraging peer referral, and providing a modest monetary incentive. Methods: Areas of high poverty were identified using census data; ethnographic/key informant interviews identified sites in those areas where the target population congregated. Black youth informed Web site design and social marketing. Content was inspirational/educational/amusing and endorsed recruitment and brand awareness. A community advisory board, participant interviews, community partner feedback, and recruitment staff involvement in the process evaluation helped refine the program in an ongoing manner. Results: During formative stages, 41 key informant/community advisory board members informed program refinement. Community partners provided venue locations (n = 65) and participant referrals. Between May 22, 2017, and February 28, 2020, 1890 men were enrolled (acceptance rate, 96.0%) with Ct infection rate of 10.2%. Overall study treatment was provided to 86.1% (71.4%–90.9%) of participants who tested positive and 28.5% (14.5%–41.5%) of their partners. Findings from in-depth interviews with participants (n = 43) led to increased treatment uptake. Conclusions: C. trachomatis community screening of young Black men was successful through collaboration with trusted community partners, by tailoring implements/marketing with participant input, reducing barriers to treatment, and providing modest monetary incentives. The Check It program can serve as a roadmap for reducing health disparities in this population.